PENGARUH KESADARAN MEREK, ASOSIASI MEREK DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PENGGUNAAN KEMBALI BRIZZI SEBAGAI JASA TRANSASKSI BERBASIS KARTU ELEKTRONIK (Studi Kasus Bank Rakyat Indonesia KCP Ketanggungan Brebes) - Raditya Mirza Bagaskara; Hari Susanta Nugraha (Universitas Diponegoro, 2019)
Brizzi is an electronic card-based transaction service owned by Bank Rakyat Indonesia. Nowadays electronic cards have become a necessity for the public, but in their use Brizzi has a problem that is the low use of Brizzi compared to electronic card-based transaction services in 2016 to 2019. The purpose of this study was to study brand awareness, brand associations and perceived quality of the decision to reuse Brizzi electronic cards at Brebes. This type of research used is explanatory research in which data collection techniques used are using a questionnaire and using accidental sampling. The sample used was 94 respondents who had been selected with criteria such as; Bank Rakyat Indonesia, whether male or female, accepts 20 years or more domiciled in Brebes, and uses Brizzi with a minimum of 6 months of use. The methodology used to analyze primary data in this study is the validity, reliability, assessment coefficient, determination coefficient, simple and multiple regression with the help of the IBM SPSS (Statistical Product and Service Solutions) version 24. The results showed the contribution of awareness, brand association and perceived quality of the decision to reuse by 87.7% while the other 12.3% related to factors other than brand awareness, brand association and perceived quality. While the rest by other factors. Successfully increasing brand awareness, brand associations and perceived quality, the higher the decision to reuse Brizzi. In addition, perceived quality has the greatest effect with a regression coefficient of 0.582. This means that increasing brand awareness, brand associations and perceptions of appropriate quality and meeting user desires can increase reuse decisions.